Volatile Compounds of Different Fresh Wet Noodle Cultivars Evaluated by Headspace Solid-Phase Microextraction-Gas Chromatography-Mass Spectrometry - WU,YAN (2020)
Abstract This study was carried out to determine the volatile compounds from four samples of fresh wet noodles and the changes in the volatile compound composition during the storage process. The ﻿﻿volatile compounds ﻿from four samples of fresh wet noodles were characterized by headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME/GC-MS). The compositions of the volatile compounds varied among fresh and cooked wet noodles made from the raw potato/wheat flour or wheat flour. A total of 194 volatile compounds were detected in the raw potato noodles, main volatiles including aldehydes, alcohols, ketones, esters and organic acids. The total volatile compounds in the potato/wheat flour noodle samples contained mainly aldehyde compounds and were greater than those in the wheat noodles. The total volatile compounds in the cooked noodle samples were greater than those in raw noodle samples. Alcohols and ketones were the least common types of volatile substances in the samples at 0 h. During storage time, alcohols and ketones were increased in volatile substances, and the amount of acids increased dramatically. The results indicated that the aroma of fresh wet noodles was affected by the storage process.